The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1210/endocr/bqaa184
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Inhibin Advances Follicle Activation and Female Puberty Onset but Blocks Oocyte Maturation in Zebrafish

Abstract: Inhibin was first characterized in mammals as a gonadal dimeric protein that inhibited pituitary follicle-stimulating hormone (FSH) secretion. As in mammals, inhibin-specific α subunit (INHA/Inha/inha) has also been characterized in teleosts; however, its functions and physiological importance in fish reproduction remain unknown. Using CRISPR/Cas9 method, we generated an inha-deficient zebrafish line and analyzed its reproductive performance. As expected, pituitary expression of fshb increased significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 73 publications
7
41
0
Order By: Relevance
“…Our previous studies proposed that EGF promotion of oocyte maturation in zebrafish was likely mediated by activins in follicles ( Pang and Ge, 2002 ), and that EGF significantly stimulated expression of activin subunits ( inhbaa , inhbab , and inhbb ) ( Pang and Ge, 2002 ; Wang and Ge, 2004a ; Tse and Ge, 2010 ; Chung and Ge, 2012 ) but suppressed that of activin binding protein follistatin ( fsta ) ( Wang and Ge, 2004a ) in cultured follicle cells. Our recent study showed that the loss of inhibin ( inha ), an antagonist of activin, advanced follicle development by promoting follicle activation or PG–PV transition, leading to precocious puberty ( Lu et al, 2020 ). This is opposite to the disruption of egfra , which blocked PG–PV transition as reported in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies proposed that EGF promotion of oocyte maturation in zebrafish was likely mediated by activins in follicles ( Pang and Ge, 2002 ), and that EGF significantly stimulated expression of activin subunits ( inhbaa , inhbab , and inhbb ) ( Pang and Ge, 2002 ; Wang and Ge, 2004a ; Tse and Ge, 2010 ; Chung and Ge, 2012 ) but suppressed that of activin binding protein follistatin ( fsta ) ( Wang and Ge, 2004a ) in cultured follicle cells. Our recent study showed that the loss of inhibin ( inha ), an antagonist of activin, advanced follicle development by promoting follicle activation or PG–PV transition, leading to precocious puberty ( Lu et al, 2020 ). This is opposite to the disruption of egfra , which blocked PG–PV transition as reported in this study.…”
Section: Resultsmentioning
confidence: 99%
“…This was further evidenced in the present study by novel phenotypes shown by egfra and inha double mutant. Although the loss of inhibin ( inha−/− ) alone accelerated follicle activation or PG-PV transition ( Lu et al, 2020 ), it could not rescue the phenotype of PG-PV blockade shown by the egfra mutant. Instead, egfra and inha double mutant induced a novel phenotype not shown by single mutants, viz .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More evidence proves that the TGF-β signaling genes, besides Amh , gsdf and Amhr2 discussed above, are critical for regulating gonadotropin signaling pathways in vertebrates. The other two TGF-β subfamily members, Activin and Inhibin, antagonize each other to regulate pituitary fshb expression and Fsh secretion in vertebrates ( 51 ). Inhibin contains a unique inhibin-specific α subunit (Inha) and shares a common β subunit (Inhba and Inhbb) with Activin to form Inhibin A, or Inhibin B. Activins are homodimers of either Inhba or Inhbb or their heterodimers.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibin contains a unique inhibin-specific α subunit (Inha) and shares a common β subunit (Inhba and Inhbb) with Activin to form Inhibin A, or Inhibin B. Activins are homodimers of either Inhba or Inhbb or their heterodimers. In mammals, Activin stimulates, and Inhibin inhibits the Fsh section ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%